2018
DOI: 10.1016/j.jns.2018.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Incident stroke among Ghanaians with hypertension and diabetes: A multicenter, prospective cohort study

Abstract: BackgroundThe burden of stroke among hypertensive and diabetic population in sub-Saharan Africa remains high. We sought to identify the risk factors associated with stroke occurrence in these high-risk population groups.MethodsA prospective cohort study involving adults with hypertension and or type II diabetes mellitus at 5 public hospitals in Ghana who were stroke-free at enrollment. Patients were followed every 2 months at clinic for 18 months and assessed clinically for first ever stroke by physicians. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 41 publications
1
22
0
2
Order By: Relevance
“…Increased BMI has been shown to lead to CKD through DM and hypertension and through other pathophysiology such as hyperfiltration leading to focal segmental glomerulosclerosis which presents with heavy proteinuria . Physical inactivity has also been associated with the occurrence of incident stroke in the present cohort and indeed among West Africans…”
Section: Discussionmentioning
confidence: 62%
“…Increased BMI has been shown to lead to CKD through DM and hypertension and through other pathophysiology such as hyperfiltration leading to focal segmental glomerulosclerosis which presents with heavy proteinuria . Physical inactivity has also been associated with the occurrence of incident stroke in the present cohort and indeed among West Africans…”
Section: Discussionmentioning
confidence: 62%
“…On a much broader scale, our previous report shows a highly prevalent but poorly controlled hypertension rate in the general population based on evidence gleaned from our HIV-negative sample. 22 This may explain why we found that HIV per se was not to be independently associated with stroke occurrence in a low endemic country such as Ghana, 44 although the burden of stroke and poor outcomes continue to rise in the subregion [45][46][47][48] due to a myriad of factors hampering the control of key CVD risk factors. 49…”
Section: Discussionmentioning
confidence: 93%
“…Overall, it is estimated that up to 70% or more of cases of diabetes are currently undiagnosed in SSA (Mbanya et al, 2010;Fasanmade and Dagogo-Jack, 2015;Pastakia et al, 2017). This is a concern as diabetes and its associated comorbidities increase cardiovascular diseases (CVD), which are responsible for approximately 70% of diabetes-related deaths (Glezeva et al, 2015;Low Wang et al, 2016;Mwita et al, 2017;Sarfo et al, 2018). It is hoped that ongoing activities across Africa (Table 1) will start to address this especially with mortality rates enhanced by uncontrolled hypertension as well as lack of control of HbA1c and lipid levels, especially low density lipoproteins (LDL-C), coupled with inactivity (U.…”
Section: Introductionmentioning
confidence: 99%